Analisis Penilaian Kinerja Ekonomi Daerah Provinsi Kepulauan Bangka Belitung Tahun 2019-2023 - Soraya Maghrisa Yasmine; Lilis Siti Badriah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The development of a region is reflected in the level of economic growth, income and welfare of its population. This research aims to analyze the economic performance of the Bangka Belitung Islands Province in 2019-2023 by using Location Quotient (LQ) Analysis, Growth Ratio Model (MRP), and Overlay Analysis. This research uses a quantitative approach with secondary data in the form of Bangka Belitung Islands Gross Regional Domestic Product (GRDP) and Indonesia's Gross Domestic Product (GDP). Based on the results of the LQ analysis, the Mining and Quarrying sector is a basic sector. The results of the MRP analysis, the Transportation and Warehousing sector produces positive RPR (+) and positive RPS (+) values, meaning that this sector both in the reference area and the study area has high growth. And based on the results of the Overlay Analysis, there are three economic sectors that are dominant and superior sectors, including the Agriculture, Forestry and Fisheries sector, the Construction Sector and the Transportation and Warehousing Sector. The government can consider the Agriculture, Forestry and Fisheries sector the Construction Sector and the Transportation and Warehousing Sector to be further developed because these sectors are potential sectors when viewed from the results of their contribution and growth.